Assessment of petrologic subtypes, subgroups, and pairing within CV chondrites in the US Antarctic meteorite collection. (8th December 2022) - Righter, Kevin; Jakubek, Ryan S.; Fries, Marc D.; Schutt, John; Pando, Kellye; Harrington, Roger
Abstract: Carbonaceous chondrites of the Vigarano group (CV) are primitive (nearly un‐metamorphosed) meteorites that provide a wealth of information about the early solar system, including constraints on chondrule formation, origin of calcium‐aluminum inclusions, stability of organic compounds, and redox conditions. The US Antarctic meteorite collection contains 119 CV samples from 15 dense collection areas (DCAs) from the TransAntarctic Mountains; these samples have been assigned a preliminary classification as CVs, but not to the subgroups oxidized A, oxidized B, and reduced. Furthermore, variation in petrologic grade can be determined non‐destructively using Raman spectroscopy. To update the classification of both subgroups and petrologic types in the collection, we have acquired magnetic susceptibility, metal and sulfide compositions, and Raman spectra. Overall, there are 55 oxidized A samples, 18 oxidized B samples, and 46 reduced samples. Several of the CVs are quite primitive (Lewis Cliffs Ice Tongue and MacAlpine Hills) but are also very small. Multiple pairing groups have been identified in the Miller Range (MIL), Queen Alexandra Range, and Larkman Nunatak DCAs, including all of the subgroups. In MIL 090981, there is evidence for multiple lithologies. We make suggested updates for all the samples, knowing that this information will help to better guide researchers interested in studying the CV chondrites in the US Antarctic meteorite collection.